1994
DOI: 10.1126/science.265.5172.625
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Organization and Time Dependence of Jupiter's Tropospheric Temperatures, 1980-1993

Abstract: The spatial organization and time dependence of Jupiter's temperatures near 250-millibar pressure were measured through a jovian year by imaging thermal emission at 18 micrometers. The temperature field is influenced by seasonal radiative forcing, and its banded organization is closely correlated with the visible cloud field. Evidence was found for a quasi-periodic oscillation of temperatures in the Equatorial Zone, a correlation between tropospheric and stratospheric waves in the North Equatorial Belt, and sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 18 publications
9
50
0
Order By: Relevance
“…Fig. 2b shows a wave pattern in the mid-NEB in the upper troposphere (p < 500 mbar), similar to that observed by previous studies [e.g., Magalhaes et al, 1990;Orton et al, 1994;Deming et al, 1997;Li et al, 2006;Fisher et al, 2016]. The warm crests have a central latitude of 13 − 15 • N, and the wave pattern is latitudinally confined to the bright belt at 10 − 17 • N (±1 • ).…”
Section: Upper Tropospheric Neb Wavesupporting
confidence: 74%
See 3 more Smart Citations
“…Fig. 2b shows a wave pattern in the mid-NEB in the upper troposphere (p < 500 mbar), similar to that observed by previous studies [e.g., Magalhaes et al, 1990;Orton et al, 1994;Deming et al, 1997;Li et al, 2006;Fisher et al, 2016]. The warm crests have a central latitude of 13 − 15 • N, and the wave pattern is latitudinally confined to the bright belt at 10 − 17 • N (±1 • ).…”
Section: Upper Tropospheric Neb Wavesupporting
confidence: 74%
“…The 2016 thermal wave (N ∼ 16 − 17) is therefore the most compact (highest wavenumber) yet observed. Intriguingly, Orton et al [1994] reported an increase in wave activity between 1988-90 and again in 1993 (compared to their 1978-1993 record), both coinciding with expansion events. The wave pattern characterized by Cassini [Li et al, 2006] also occurred during an expansion.…”
Section: Upper Tropospheric Neb Wavementioning
confidence: 99%
See 2 more Smart Citations
“…Wavenumber IH waves were found at equatorial latitudes at depths between PUH mbar and I bar by several authors (Magalhaes et al, 1989;Orton et al, 1994;Harrington et al, 1996;Deming et al, 1997). The source of the waves is unknown and hypothesis range from vertical propagation of Rossby waves (Orton et al, 1994) and mixed Rossbygravity waves (Deming et al, 1997), to connection with the plumes in the equatorial hot-spots (Ortiz et al, 1998;Showman and Dowling, 2000) or association with deep convective cells (Magalhaes et al, 1989). The near stationary appearance of these waves with respect to system III implies possibly a dynamical link between the interior bulk rotation of the planet (Irwin, 2003).…”
Section: The Thermal Structurementioning
confidence: 99%